Sexual Selection in Relation to Pest-Management Strategies - Boake, Christine R. B.; Shelly, Todd E.; Kaneshiro, Kenneth Y. (Annual Review of Entomology, 1996)
The application of principles derived from the sexual selection literature can assist attempts to subvert the normal mating behavior of pests. Sexual selection encompasses both intermale competition for access to females and female choice of mates. It can operate during long-range attraction and short-range courtship, as well as after copulation. We review the major aspects of sexual selection and illustrate their application to pheromonal and SIT pest-management programs. Pheromones are important both in long-range attraction and in close-range mate choice; parapheromones may be very useful in pest management because of their influence on male mating success. Sexual selection theory provides a scheme for studying the normal mating behavior of a pest species and thus determining which attributes of the mass-reared sterile males are critical to their success with wild females. We hope that our review will suggest novel ways of attacking pests as well as encourage behavioral ecologists to study pest species.
Keywords: mate choice